Development of the School System and Pedagogics in Serbia During the First Half of 20th Century – Major Scientific and Societal Influences - Petrović, Jelena S.; Dobrosavljević, Danica M.; Simić, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The main objective of this paper was to analyse the development of the school system and the science of education in the first half of the 20th century. Different societal circumstances were taken into consideration, including political, economic, and cultural, as well as pedagogical trends that dominated the educational scene at that time. In order to follow those influences more easily, we analysed the development of schools and pedagogical science through two periods that could easily be distinguished. The first period begins at the end of the 19th century and last until the beginning of the World War I. During this period we can witness the rapid development of the school system. The other period is embedded between two world wars and is marked by the advancement of theory and development of different pedagogical approaches.
Keywords: The Work School; New Education Movement; Herbartian pedagogy; development of Serbian school system